Effect of Additional Aloe Vera (Aloe vera) on Artificial Feeds to Blood Cell Profile and Growth of Milkfish Seed (Chanos chanos) - Linayati Linayati; Nur Tri Jayanto; Tri Yusufi Mardiana; Muhammad Zulkham Yahya (Department of Aquaculture, 2022)
Problems in cultivating milkfish are disease outbreaks and the high cost of feed. Therefore, a breakthrough is needed to overcome this problem by adding medicinal plants, namely aloe vera, to the feed. This study aims at determining the effect of adding aloe vera to artificial feed on the blood cell profile and growth of milkfish seed. The research method used was a complete randomized design with 4 (four) treatments and 3 (three) replications. The treatments on the test feed used were: A, (giving aloe vera as much as 0 g/kg feed), B (giving aloe vera as much as 5 g/kg feed), C (giving aloe vera as much as 10 g/kg feed), and D (giving aloe vera as much as 15 g/kg feed). The results showed that blood glucose values were still within the normal range. The lowest value in treatment was A, which was 42 mg/dL, and the highest in treatment was D, which was 66 mg/dL. The lowest Hb value was found in treatment A (5.1 g/dL), and the highest was 7.2 g/dL, found in treatment D. The highest average growth rate was obtained in treatment D with increasing biomass of 3.81g. While the lowest growth was obtained in treatment A which resulted in average growth of 2.06g. Water quality during the study was suitable for milkfish rearing media, namely temperature of 27 - 31°C, pH of 7.2 -,7,8, and salinity of 25 - 27 ppt.